VULNERABILITY IN ADHERENCE TO PROPHYLAXIS OF VERTICAL TRANSMISSION OF HIV - Tassiane Ferreira Langendorf; Stela Maris Mello Padoin; Cristiane Cardoso Paula; Clarissa Bohrer Silva (Universidade Federal do Paraná, 2012)
This integrative review aimed to evaluate the evidence available in scientific articles on factors which influence the adherence to prophylaxis of vertical transmission of the Human Immunodeficiency Virus (HIV). It was developed in the LILACS and MEDLINE databases with time cut-off points of 1994-2010; 29 articles were submitted to thematic content analysis, with theoretical categorization according to the framework of vulnerability. The results indicate that, on an individual plane, the women take decisions which reflect positively or negatively on adherence; on the social plane, difficulty in accessing information is evidenced. In the programmatic plane there is the need for professional training/qualification for care, combined with public policies; the planes of vulnerability maintain a close relationship with each other. There is the possibility of mediation, by the nurse, of information between the programmatic plans and the individual, through health education, viabilizing informed decisions relating to health care in prophylaxis of vertical transmission of the virus.